(untitled) (Journal of Preventive and Social Medicine, 2023)
Background: Acid Violence is one of the worst form of violation of basic human rights and a major public health issue. Though the prevalence has dropped dramatically after the enactment of two important laws against this crime in Bangladesh the victims in this country are still leading a disastrous life. The present study aimed to identify the score of Quality of life and to find out the coping strategies among acid victims. Methods: This cross sectional study was conducted from July to September, 2019 among purposively selected 101 acid victims in four districts of Bangladesh. Data was collected through face-to-face interview by using SF-36 Health Related Quality of Life scale and Brief Cope Inventory (Carver). Results: About 82% of the acid victims were female, 51.49% were illiterate, income of 69.3% respondents were below 5000 Taka, 80.2% got married before the age of 18 years. Apart from Physical functioning (63.66±32.124) and Social functioning (60.89±39.198), all the domain of the QOL score remains below 30, the score of General health is 27.97±30.791. Active coping was followed a lot (43%) among all the other coping strategies. There was positive correlation with active coping and social functioning(r=0.359, p=0.000) and physical functioning (r=0.288, p=.003). Conclusion: Even after many years of the violence, the acid victims have not regained a good quality of life. Community support and frequent motivational campaigns can help the acid victims to cope up with their situation more positively and thus improve their quality of life. JOPSOM 2021; 41(1):19-24